Star shearing season: transient signals in wave-like dark matter experiments from black hole formation - De Giorgi, Arturo; Jaeckel, Joerg (The European physical journal. C, Particles and fields, 2025)
Ordinary matter coupled to light weakly interacting bosons can lead to the formation of a macroscopic bosonic field in the vicinity of large matter concentrations such as ordinary or neutron stars. When these objects are turned into black holes due to a supernova or a binary merger this “hair” could be “shorn” off. Part of the field configuration would then be released leading to an outgoing field wave. For small masses this field transient remains rather compact and can induce a transient signal in experiments, in particular those that look for wave-like dark matter. This signal can be correlated with the corresponding astrophysical signal of the event. In this note, we consider a variety of couplings and the associated signals and estimate the corresponding sensitivities.
Gesehen am 29.07.2025